Medical xenophobia and healthcare exclusion of refugees and migrants in Africa: A scoping review - Alexis Harerimana; Julian David Pillay; Gugu Mchunu (Journal of Migration and Health, 2025)
Background: Medical xenophobia, manifesting as discrimination and exclusion from healthcare based on nationality or documentation, threatens migrants’ and refugees’ rights and public health. This study maps evidence of what is known about medical xenophobia and healthcare exclusion of refugees and migrants in Africa. Methodology: The framework established by Levac et al. offered a structured method for executing this scoping review. This research implemented a comprehensive search strategy to identify academic papers and grey literature. Databases such as CINAHL, Emcare, Medline Ovid, Scopus and Web of Science were utilised, focusing on the period from 2014 to 2024. A total of 20 articles were selected for data extraction and thematic synthesis. Results: The scoping review identified pervasive medical xenophobia and exclusion of refugees and migrants in African healthcare systems. This phenomenon included discriminatory attitudes from healthcare personnel, cultural insensitivity, verbal abuse, poor or denial of care due to documentation status of refugees and migrants, financial exploitation, and linguistic discrimination in healthcare settings. Refugees and migrants often avoided healthcare services due to fear of harassment or deportation, worsening their physical, mental and maternal health outcomes. Interventions highlighted in the literature encompassed policy reforms, cultural sensitivity training for providers, community engagement, enhanced service accessibility, and ongoing monitoring to address systemic inequalities. Conclusion: Addressing healthcare access inequities for refugees and migrants necessitates structural reforms to ensure accountability for inadequate treatment, uphold human rights and promote equity and culturally and linguistically inclusive practices.